Prevalence of Primary Aldosteronism in Patient’s Cohorts and in Population-based Studies – A Review of the Current Literature - Hannemann, A.; Wallaschofski, H. (Hormone and Metabolic Research, 2012)
There is an ongoing controversy on the prevalence of primary aldosteronism (PA). We aimed to update a meta-analysis published in 2008, that compiled studies reporting the prevalence of positive ARR screening tests and PA. We therefore reviewed original studies published in 2008 or later to examine whether current reports provide similar, higher or lower prevalences of elevated ARRs or PA than reports included in the original meta-analysis. A systematic review of English articles using PubMed was conducted. Search and extraction of articles were performed by one review author; the second review author checked all extracted data. We identified 11 eligible studies. The updated, weighted mean prevalences of elevated ARRs and PA in primary care (prevalence of high ARRs 16.5%; prevalence of PA 4.3%) and referred patients (prevalence of high ARRs 19.6%; prevalence of PA 9.5%) were only marginally different from the mean values obtained in the original meta-analysis. Among the current studies the maximum values for the prevalence of elevated ARRs and PA were substantially lower than among the older studies. Our results confirm the main conclusions from the original meta-analysis. The prevalence of PA increases with the severity of hypertension and the inclusion of current study results did not alter the mean prevalences of elevated ARRs and PA in primary care and referred patients. Additionally, we found that current studies focus increasingly on patients in referral centers or special subgroups, while the prevalence of PA in the general hypertensive population is yet unknown.
Keywords: aldosteronism; aldosterone-to-renin ratio; hypertension; meta-analysis; prevalence; renin-angiotensin-aldosterone system